Description and Impact of a Comprehensive Multispecialty Multidisciplinary Intervention to Decrease Opioid Prescribing in Surgery. Issue 3 (September 2019) - Kaafarani, Haytham M. A.; Eid, Ahmed I.; Antonelli, Donna M.; Chang, David C.; Elsharkawy, Ahmed E.; Elahad, Joana Abed; Lancaster, Elizabeth A.; Schulz, John T.; Melnitchouk, Serguei I.; Kastrinakis, William V.; Hutter, Matthew M.; Masiakos, Peter T.; et al.
Abstract : Introduction: Diversion of excess prescription opioids contributes to the opioid epidemic. We sought to describe and study the impact of a comprehensive departmental initiative to decrease opioid prescribing in surgery. Methods: A multispecialty multidisciplinary initiative was designed to change the culture of postoperative opioid prescribing, including: consensus-built opioid guidelines for 42 procedures from 11 specialties, provider-focused posters displayed in all surgical units, patient opioid/pain brochures setting expectations, and educational seminars to residents, advanced practice providers, residents and nurses. Pre- (April 2016–March 2017) versu post-initiative (April 2017–May 2018) analyses of opioid prescribing at discharge [median oral morphine equivalent (OME)] were performed at the specialty, prescriber, patient, and procedure levels. Refill prescriptions within 3 months were also studied. Results: A total of 23, 298 patients were included (11, 983 pre-; 11, 315 post-initiative). Post-initiative, the median OME significantly decreased for 10 specialties (all P values < 0.001), the percentage of patients discharged without opioids increased from 35.7% to 52.5% ( P < 0.001), and there was no change in opioids refills (0.07% vs 0.08%, P = 0.9). Similar significant decreases in OME were observed when the analyses were performed at the provider and individual procedure levels. Patient-level analyses showed that the preinitiative race/sex disparities in opioid-prescribing disappeared post-initiative. Conclusion: We describe a comprehensive multi-specialty intervention that successfully reduced prescribed opioids without increase in refills and decreased sex/race prescription disparities.